Analisis Struktur dan Pola Berjalan Robot Humanoid Menggunakan Metode Inverse Kinematic pada MATLAB - Muhammad Prabu Mutawakkil; Rizal Maulana; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Today, the development of robot was growing so quick, one of them is Humanoid Robot. As like the name, Humanoid Robot have feet that have walks and shaped like human does. This robot has two feet that consisted of three DoF (Degree of Freedom) for one of each foot. Humanoid Robot use Inverse Kinematic method to walk which using end of effector as the coordinate. The result that suggested from Inverse Kinematic method were the coordinate destination. The implementation of Humanoid Robot we do it on MATLAB and Simulink to test about the mechanism from the robot if it were applied on software. The difference was shown for the avability of the hardware and its tools and the result sometimes would be different if applied in real world. There are some differences when robot got implemented compared with physical ones. From this research, there are 11 trials to measure about success rate for robot to able to walk successfully from the robot if their variables from physical appereances were modified. As the result, there are 54,54% success rate compared with the original variables that got from trial and error.